KAJIAN YURIDIS SYARAT-SYARAT PENUNDAAN PELAKSANAAN KEPUTUSAN TATA USAHA NEGARA DALAM SENGKETA TATA USAHA NEGARA - I KADEK ADI SURYA; I WAYAN ANTARA; IDA BAGUS WIRYA DHARMA (Universitas Mahasaraswati K. Mataram, 2023)
The purpose of the State Administrative Court is basically to protect the legal interests of the community from arbitrary actions or abuse of authority by the government, given the vast scope of government employment. The State Administrative Court is held to resolve disputes between the Government and its citizens, namely disputes that arise as a result of Government actions deemed to have violated the rights of its citizens. elements of the state law, so that in this study the aim is to find out in the process of delaying the implementation of State Administrative decisions in State Administrative disputes, then in research using normative legal research research methods which can be defined by a process to find a rule of law, legal principles, as well as legal doctrines to answer the legal issues at hand, the result of this research is that the conditions for requesting a postponement of the implementation of State Administrative Decisions can be seen from the provisions of article 67 of Law Number 9 of 2004 and Circular Letter of the Supreme Court No. or 2 of 1991 concerning instructions for the implementation of several provisions in Law Number 5 of 1986 concerning the transition of state administration. So that in postponing a State administrative decision it can be granted if it fulfills the following conditions: a). a request for postponement of the implementation of a State administrative decision can be filed simultaneously in a lawsuit, b) there is a very urgent situation which results in the interests of the plaintiff being greatly harmed if the state administrative decision being sued is still carried out and c). there is no public interest in the framework of development that requires the implementation of the decision.